Tissue-Specific Metabolite Profiling of Turmeric by Using Laser Microdissection, Ultra-High Performance Liquid Chromatography-Quadrupole Time of Fight-Mass Spectrometry and Liquid Chromatography-Tandem Mass Spectrometry. Issue 5 (October 2014) - Jaiswal, Yogini; Liang, Zhitao; Ho, Alan; Chen, Hubiao; Zhao, Zhongzhen
Curcuma longa L. is recognized for its therapeutic and culinary uses both in Ayurveda and traditional Chinese medicine and is considered to be a boon to mankind. It has been extensively studied for its benefits and still continues to be an important drug with continued potential for further exploration and research. We studied the tissue-specific distribution of secondary metabolites to establish the validity of the use of rhizome samples from India and China, as substitutes for each other, based upon their metabolite profiles and curcumin contents. Laser microdissection was used for the isolation of microscopic tissues, such as cork, cortex and leaf-trace vascular bundles from rhizomes. Metabolite profiling was carried out by ultra-high performance liquid chromatography-quadrupole time of fight-mass spectrometry and curcumin content was estimated by a method validated as per the Harmonized Tripartite Guidelines. The cortex and cork revealed the presence of a higher number of secondary metabolites than in the leaf-trace vascular bundles. The curcumin contents in rhizome samples from both the countries, estimated with the help of a precise and accurate validated method, were found to be comparable. Based on the results, we conclude that turmeric rhizomes grown in India and China are qualitatively and quantitatively indistinguishable and therefore can be used as substitutes. The developed method can be widely applied for microscopic identification, authentication and analysis of the distribution of phytoconstituents in other botanical species of interest or of species with a significant commercial and therapeutic value.